Mucormycosis: Issues, Pathophysiology, Diagnosis and Treatment - Regmi, Sagar; Mahato, Premlal (Journal of Karnali Academy of Health Sciences, 2023)
Mucormycosis (Black fungus) is an infection caused by opportunistic fungi of order Mucorales affecting the immune-compromised individuals. Cases of Aspergillus and Candida (White fungus) were also reported. The cases of fungal co-infection in COVID-19 patients are increasing globally affecting mainly diabetic patients and individuals that have undergone corticosteroid therapy. Iron metabolism and hypoxia plays an important role in pathophysiology of this disease. Mucormycosis causes thrombosis of blood vessels hindering the blood circulation causing black discoloration of affected site. Histopathological examination of specimen is the most effective way of its diagnosis. Surgical removal of affected site is the best treatment practice in rhino-orbital and cutaneous cases whereas lipid formulation of Amphotericin B is effective in other forms of fungal infection.